The Effect of E-LKPD-Assisted Problem Based Learning Model on Students' Problem-Solving Skills and Self-Confidence in Vocational School Mathematics Learning - Andhika Matsubara, Septien; Hamdi , Syukrul (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This study aims to analyze the influence of the Problem-Based Learning (PBL) model assisted by e-LKPD on students’ problem-solving abilities and self-confidence in vocational high schools. Specifically, the objectives are: (1) to examine the simultaneous effect of the PBL model assisted by e-LKPD on both variables, (2) to determine its effect on problem-solving ability, and (3) to evaluate its effect on self-confidence. A quantitative approach with a quasi-experimental pretest–posttest control group design was applied. The population consisted of all 10th-grade students at SMK Negeri 1 Tarakan, while the sample was selected using purposive sampling, resulting in class X Marketing 1 (35 students) as the experimental group and class X Culinary 2 (34 students) as the control group. Research instruments included a problem-solving test and a self-confidence questionnaire. Hypothesis testing utilized Hotelling’s T² and independent sample t-tests. The findings showed that 97% of students in the experimental class met the Learning Objectives Mastery (KKTP), compared to only 18% in the control group. Improvement in the experimental group was categorized as high, whereas in the control group it was moderate. Self-confidence also increased significantly in the experimental group, with most students moving from low to high categories. Hotelling’s Trace (Fcount = 77.109, p < 0.001) and t-tests confirmed significant effects on both problem-solving (tcount = 11.657) and self-confidence (tcount = 8.140), proving that the PBL model assisted by e-LKPD effectively enhances students’ abilities and confidence.